2012
DOI: 10.1175/2011bams3095.1
|View full text |Cite
|
Sign up to set email alerts
|

The “Year” of Tropical Convection (May 2008–April 2010): Climate Variability and Weather Highlights

Abstract: The representation of tropical convection remains a serious challenge to the skillfulness of our weather and climate prediction systems. To address this challenge, the World Climate Research Programme (WCRP) and The Observing System Research and Predictability Experiment (THORPEX) of the World Weather Research Programme (WWRP) are conducting a joint research activity consisting of a focus period approach along with an integrated research framework tailored to exploit the vast amounts of existing observations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(104 citation statements)
references
References 139 publications
2
102
0
Order By: Relevance
“…These IWV areas match the areas of high moisture transport from the tropics to the extratropics as found by Knippertz et al (2013). Waliser et al (2012) also found that the maximum number of ARs occurred in the northeastern Pacific. In regional studies over longer periods, about 15 landfalling ARs per year were counted in California (Neiman et al, 2008), and on average about 8-10 persistent winter ARs (of at least 18 h duration) affected Great Britain (Lavers et al, 2012).…”
Section: A Climatological View Of Arssupporting
confidence: 82%
See 1 more Smart Citation
“…These IWV areas match the areas of high moisture transport from the tropics to the extratropics as found by Knippertz et al (2013). Waliser et al (2012) also found that the maximum number of ARs occurred in the northeastern Pacific. In regional studies over longer periods, about 15 landfalling ARs per year were counted in California (Neiman et al, 2008), and on average about 8-10 persistent winter ARs (of at least 18 h duration) affected Great Britain (Lavers et al, 2012).…”
Section: A Climatological View Of Arssupporting
confidence: 82%
“…The moisture in an AR has two origins (Bao et al, 2006): (1) local moisture convergence along the cold front of the extratropical cyclone, and (2) direct poleward transport of tropical moisture. The different precipitation regimes observed in an AR event include (Matrosov, 2013) "cold" rainfall (mostly formed by ice precipitation above the freezing level for more northern latitudes); "warm" rainfall (limited amounts of ice in precipitation for temperatures above the freezing level); and regions of mixed precipitation with both warm and cold Waliser et al (2012) and Zhu and Newell (1998). White contours showed the continental areas where there are reported cases of ARs linked with extreme precipitation and floods (listed in Supplementary Table III).…”
Section: Structure Of An Ar: Observation and Modelingmentioning
confidence: 99%
“…To estimate the structure and amplitude of the model tendencies for a TC, we use the tendencies from the ECMWF Year Of Tropical Convection (YOTC) data set (Waliser et al, 2011). During the YOTC period, the tendencies from the parametrization schemes of the forecast model of ECMWF were archived every 3 h for 36 h. The resolution of the YOTC calculations is slightly higher (TL799; ≈ 25 km) than the resolution of our ensemble forecasts.…”
Section: Composite Structurementioning
confidence: 99%
“…(Li et al, 2013). The models account for ice clouds in radiation calculations but often ignore the radiative fluxes and heating rates from frozen precipitation in the air (Waliser et al, 2012). Hence, remote sensing of microphysical properties in frozen precipitation and their connection to ice clouds above and surface precipitation, like this work, will provide a valuable surrogate for climate models in representing cloudprecipitation processes.…”
Section: Introductionmentioning
confidence: 99%